Thermochemical oxidation of phenolic-laden liquid effluent models. Issue 5 (30th August 2007) - Benali, M.; Guy, C.
Abstract : The paper presents a novel atmospheric free-radical thermochemical oxidation (TCO) process in an aqueous phase for decontamination of industrial liquid effluents from organic toxic substances, in particular the refractory organic pollutants such as phenols. Its original concept is based on a direct contact between a contaminated liquid stream and the flame of a gas-fired burner containing free radicals such as OH ·, H ·, CH3 ·, and CHO · . Despite a direct contact of the contaminated liquid with the flame, the evaporation was less than 6% at the separator outlet where liquid temperatures ranged from 60 to 70 °C. A prototype of the 50 kW reactor operated in a continuous mode with the phenol concentration ranging from 200 to 20 000 mg/L was proven to process from 200 to 300 L/h of the contaminated model liquid. Experimental results show a final destruction efficiency of over 98%. Kinetics of phenol oxidation in TCO shows that the induction period can be avoided by injection of a small amount of hydrogen peroxide in the contaminated effluent feeding tank.